Urgent transcatheter edge-to-edge repair for severe mitral regurgitation with flail leaflet in critically Ill patients - Perel, Nimrod; Amsalem, Itshak; Gilad, Or; Hitter, Rafael; Maller, Tomer; Asher, Elad; Harari, Emanuel; Marmor, David; Carasso, Shemy; Dvir, Danny; Glikson, Michael; Shuvy, Mony (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Degenerative mitral valve disease (DMR) is a common valvular disorder, with flail leaflets due to ruptured chordae representing an extreme variation of this pathology. Ruptured chordae can present as acute heart failure which requires urgent intervention. While mitral valve surgery is the preferred mode of intervention, many patients have significantly elevated surgical risk and are sometimes considered inoperable. We aim to characterize patients with ruptured chordae undergoing urgent transcatheter edge-to-edge repair (TEER), and to analyze their clinical and echocardiographic outcomes. Methods: We screened all patients who underwent TEER at a tertiary referral center in Israel. We included patients with DMR with flail leaflet due to ruptured chordae, and categorized them into elective and critically ill groups. We evaluated the echocardiographic, hemodynamic, and clinical outcomes of these patients. Results: The cohort included 49 patients with DMR due to ruptured chordae and flail leaflet, who underwent TEER. Seventeen patients (35%) underwent urgent intervention and 32 patients (65%) underwent an elective procedure. In the urgent group, the average age of the patient was 80.3, with 41.8% being female. Fourteen (82%) received noninvasive ventilation, and three patients (18%) required invasive mechanical ventilation. One patient died due to tamponade, while echo evaluation of the other 16 patients demonstrated successful reduction of ≥2 in the MR grade. Left atrial V wave decreased from 41.6 mmHg to 17.9 mmHg (p<0.001), and the pulmonic vein flow pattern changed from reversal (68.8%) to a systolic dominant flow in all patients (p=0.001). After the procedure, 78.5% of patients improved to New York Heart Association (NYHA) class I or II (p<0.001). There was no significant difference in the overall mortality between the urgent and elective groups, with similar 6 month survival rates for each group. Conclusion: Urgent TEER in patients with ruptured chordae and flail leaflets can be safe and feasible with favorable hemodynamic, echocardiographic, and clinical outcomes